Nematode Pheromones as Key Mediators of Behavior, Development, and Ecological Interactions - Xi Zheng; Junjie Liu; Xin Wang (Biomolecules)
Plant parasitic nematodes cause huge economic losses to agriculture and forestry every year, and chemical insecticides destroy the ecological environment. Researching the mechanism by which small-molecule signaling substances regulate nematode behavior and development is important for developing environmentally friendly biological control agents. Nematode pheromones are essential chemicals signaling intraspecies and interspecies communication, regulating development, reproduction, and social behavior. Their structural diversity enables ecological adaptation and cross-kingdom interactions, influencing fungal predation and plant immunity. This review focuses on the classification, function, and regulatory mechanisms of nematode pheromones, interspecific signal transmission, and biosynthesis pathways. We pay special attention to their potential as environmentally friendly biological control agents as well as the challenges currently encountered in their application.